Bilateral Gonadoblastoma in a girl with Turner syndrome: a case report - Urbina, Claudia (2015)
A case of bilateral gonadoblastoma in a yearold girl with Tumer's syndrome and positive SRY antigen is presented. As the kariotype showed 45 X / 46 XY mosaicism, bilateral gonadal biopsy by laparoscopy was done. Pathology confirmed bilateral gonadoblastoma and bilateral gonadectomy was then performed, with satisfactory post operative evolution. Prophylactic gonadectomy is recommended in cases of Turner’s syndrome with positive SRY antigen.